UNDERSTANDING MULTIPLE INTELLIGENCES PRESENT IN THE SCHOOL ENVIRONMENT ACCORDING TO GARDNER'S THEORY (REMUNOM, 2025)
The present research aimed to review and analyze, in a narrative way, studies and publications that address the different multiple intelligences identified in the school environment, with the aim of understanding the types of intelligences. To this end, a bibliographic research of the narrative review type was developed, with a qualitative approach through the study of scientific articles and other academic works found on the search platform “Google Scholar” using the terms “Theory of Multiple Intelligences”. The analysis was carried out in an interpretative way. As a result, it was found that the theory of multiple intelligences argues that human intelligence is composed of different abilities, and not by a single general capacity. Among these are linguistic, logical-mathematical, spatial and musical. Also noteworthy are the corporal-kinesthetic, interpersonal and intrapersonal. Each corresponds to different ways of learning, acting and expressing oneself. Naturalistic intelligence completes the group, focusing on the connection with nature. It is considered that studying multiple intelligences allows recognizing the individualities of students and expanding their ways of learning. With this, the school can offer a more intentional and comprehensive education.